Comparison of the early development of the professional values for nursing students in the traditional program and the second‐degree program: a longitudinal study - Hui‐Ping Lin; Tsai‐Hsiu Chang; Hsiu‐Fang Lee; Yu‐Hsia Tsai; C.W Chang; Hui‐Chu Chiang; Hsueh‐Erh Liu (Nursing Open, 2022)
Abstract Aim This study aims to compare the early development of professional value between the students in the traditional programme (BSN) and those in the accelerated BSN (ABSN) programmes. Design A longitudinal design was conducted. Methods Data were collected from three schools of nursing during one academic year. A total of 117 BSN students and 101 ABSN students completed the survey of demographic information and the Nurses’ Professional Values Scale–Revised questionnaires. All data were analysed by IBM SPSS‐Statistics 22. Results Results showed that, in the beginning of the first professional nursing course, both students in the BSN and the ABSN programmes reported similar level of professional values. However, after one academic year, the changes in the professional value varied both between these two programmes and among the three different nursing schools. The increased professional value in school A represented the possibility for students to improve during their first‐year professional nursing programme. As educators, we should redesign our teaching strategies according to the different conditions of students in each programme.